A SURVEY OF AWARENESS AND PRACTICES OF INFORMED CONSENT AMONG DENTISTS IN RAWALPINDI AND ISLAMABAD, PAKISTAN - Shaista Rafi; Hina Khan; Muhammad Hamza Hussain; Hira Aslam; Yousra Khan; Hala Hidayat (Pakistan Oral & Dental Journal, 2024)
Objective: The aim was to determine the awareness and practices of dental professionals about informed consent among various levels of qualification. A total of 129 dentists from Rawalpindi and Islamabad were included by convenience sampling technique.Methodology: Dentists practicing clinically in Rawalpindi and Islamabad were included. Undergraduate dental students, dental technicians and dental assistants were excluded.Results: Data was collected using an especially developed questionnaire, and analyzed using SPPS through chi-square tests. The mean age was 33.89Â±7.57 years. A total of 126 dentists (96.67%), including 45 females (34.88%) and 84 males (65.12%), were familiar with informed consent. The most frequently reported â€œbasic element of Informed Consentâ€ was confidentiality (n=50, 38.76%), followed by treatment alternatives (n=33, 25.58%), and all of these (n=29, 22.48%). The most frequently reported â€œmain purpose of Informed Consentâ€ was legal (n=128, 18.12%), followed by ethical (n=45, 35.16%), and all of these (n=51, 39.72%). Most of the participants said they take Informed Consent prior to treatment (n=103, 79.84%), stating that it is not a waste of time (n=69, 53.49), that they take it verbally (n=107, 82.95%), and that the minimum age to sign Informed Consent by oneself is above 18 years (n=109, 84.5%). Only 6 (4.65%) said they provide a copy of Informed Consent to patients.Conclusion: There was lack of awareness and good practices among dental professionals regarding the process of taking informed consent. More qualified dentists reported better awareness and practices compared to less qualified dentists. Only few dental professionals have the habit of obtaining written Informed Consent.
Keywords: Informed consent; dentists; dental professionals; written informed consent